Implementation of a Green Economy: Coal Industry, Electric Vehicles, and Tourism in Indonesia - Niu Haitao (Dinasti Publisher, 2022)
Implementing a Green Economy is based on global climate change, which is increasingly difficult to predict. Climate change often makes economic activity hampered, both domestically and globally. Many things cause climate change, namely: greenhouse emissions, the use of fossil energy as fuel, and also the manufacturing industry, which, when carrying out its production activities, produces exhaust emissions. The occurrence of climate change is indeed very detrimental to all human beings with the occurrence of climate change. All of us must play a role in overcoming the problem of climate change. For this reason, countries in the world have begun to switch to using renewable energy, which previously used fossil energy such as new stone to meet global energy needs. In this study, researchers determine the object of business actors, especially in the coal sector, electric vehicles, and tourism. Then the research method used is the Descriptive Qualitative Method by reviewing relevant previous articles. The results of this research are: 1) Green Economy plays an essential role in overcoming climate change and global warming, 2) Coal Industry Sustainability is affected by green economy policies, 3) Electric Vehicles play a role in the success of the policy. Green economy.